Haematological and Biochemical Parameters of Blood in Patients after BIOS of the Tibia Using Bioinert and Biodegradable Implants Based on Magnesium Alloy MA-10 - Yatsun, E. V.; Golovakha, M. L.; Maslennikov, S. O.; Makyeyeva, L. V.; Яцун, Євген Володимирович; Головаха, Максим Леонідович; Масленніков, Сергій Олегович; Макєєва, Людмила Валеріївна (My University, 2022)
Nowadays, the search for new artificial materials to replace damaged tissues and organs is becoming increasingly important. Biodegradable materials occupy an honorable place among medical materials. Depending on the purpose, biodegradable implants should be gradually replaced by living tissue and function over a given period of time, as well as not have a negative impact on surrounding tissues and the body as a whole. Magnesium-based alloys are considered promising. Clinical studies of the dynamics of a number of key biochemical parameters that characterize the reactive response and regenerative processes in the body are of scientific and practical importance. The aim of the research was to study the laboratory - biochemical parameters of blood in patients after BIOS of the tibia using bioinert and biodegradable implants based on magnesium alloy MA-1036 patients with tibial fractures were operated in the traumatology department of MNCE “CH of Emergency and Urgent Medical Aid” in Zaporizhzhia. After closed repositioning, the tibial BIOS was performed using biodegradable alloy screws. Blood sampling for biochemical and cytological studies was performed before and in 2, 4 weeks, 2 and 4 months after surgery. Biodegradable magnesium alloy MA-10 (TU U 24.4- 14307794-270: 2018) certified for use in medicine. The study of the total bilirubin dynamics in blood plasma showed that the maximum values of the indicator accompany the acute period of the pathological process. From the second week, slight fluctuations in á-amylase activity were detected, which is most likely due to the energetic support of the inflammatory process and the regeneration of damaged tissues. The use of magnesium alloy for the manufacture of screws showed stable enzyme activity for 4 weeks. In the group of patients who used magnesium alloy implants immediately after surgery, there was a significant (pdH0.05) increase in AST / ALT by 44%, compared with the initial value of the de Ritis coefficient, not by increasing the activity of AST, but by reducing activity ALT. The undulating dynamics of ESR, fibrinogen B and total bilirubin in the blood of patients of both groups reflects the stages of the reparative process. The bioinertness and expediency of using implants made of biodegradable magnesium alloy MA-10 in the dynamic BIOS for diaphyseal fractures of the tibia are substantiated.
Keywords: Biodegradation; Magnesium alloy; Inflammation; Blocking intramedullary osteosynthesis